Human Fat-Derived Mesenchymal Stem Cells Xenogenically Implanted in a Rat Model Show Enhanced New Bone Formation in Maxillary Alveolar Tooth Defects - Andrew Wofford; Austin Bow; Steven Newby; Seth Brooks; Rachel Rodriguez; Tom Masi; Stacy Stephenson; Jack Gotcher; David E. Anderson; Josh Campbell; Madhu Dhar (Stem Cells International)
Background. Due to restorative concerns, bone regenerative therapies have garnered much attention in the field of human oral/maxillofacial surgery. Current treatments using autologous and allogenic bone grafts suffer from inherent challenges, hence the ideal bone replacement therapy is yet to be found. Establishing a model by which MSCs can be placed in a clinically acceptable bone defect to promote bone healing will prove valuable to oral/maxillofacial surgeons. Methods. Human adipose tissue-derived MSCs were seeded onto Gelfoam® and their viability, proliferation, and osteogenic differentiation was evaluated in vitro. Subsequently, the construct was implanted in a rat maxillary alveolar bone defect to assess in vivo bone healing and regeneration. Results. Human MSCs were adhered, proliferated, and uniformly distributed, and underwent osteogenic differentiation on Gelfoam®, comparable with the tissue culture surface. Data confirmed that Gelfoam® could be used as a scaffold for cell attachment and a delivery vehicle to implant MSCs in vivo. Histomorphometric analyses of bones harvested from rats treated with hMSCs showed statistically significant increase in collagen/early bone formation, with cells positive for osteogenic and angiogenic markers in the defect site. This pattern was visible as early as 4 weeks post treatment. Conclusions. Xenogenically implanted human MSCs have the potential to heal an alveolar tooth defect in rats. Gelfoam®, a commonly used clinical biomaterial, can serve as a scaffold to deliver and maintain MSCs to the defect site. Translating this strategy to preclinical animal models provides hope for bone tissue engineering.